2011
DOI: 10.1194/jlr.m007104
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated FAs prevent palmitate-induced LOX-1 induction via inhibition of ER stress in macrophages

Abstract: Palmitic acid (PA) upregulates oxidized LDL receptor-1 (LOX-1), a scavenger receptor responsible for uptake of oxidized LDL (oxLDL), and enhances oxLDL uptake in macrophages. However, the precise underlying mechanism remains to be elucidated. PA is known to induce endoplasmic reticulum (ER) stress in various cell types. Therefore, we investigated whether ER stress is involved in PA-induced LOX-1 upregulation. PA induced ER stress, as determined by phosphorylation of PERK, eIF2α, and JNK, as well as induction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 39 publications
2
33
0
3
Order By: Relevance
“…Both saturated fatty acids and hypoxia have been shown to induce the unfolded protein response (21,22), which activates JNK in an IRE1-dependent manner (42,43). Although palmitate increased phosphorylation of IRE1 and transcript levels of GRP78 and CHOP in macrophages, neither of these were enhanced further under hypoxia.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Both saturated fatty acids and hypoxia have been shown to induce the unfolded protein response (21,22), which activates JNK in an IRE1-dependent manner (42,43). Although palmitate increased phosphorylation of IRE1 and transcript levels of GRP78 and CHOP in macrophages, neither of these were enhanced further under hypoxia.…”
Section: Discussionmentioning
confidence: 88%
“…Both saturated fatty acids and hypoxia have been shown to induce the unfolded protein response, which can activate the MAPK and NF-B signaling pathways (21,22). We questioned whether hypoxia heightens palmitatetriggered ER stress.…”
Section: Hypoxia Enhances Palmitate-induced Pro-inflammatory Cytokinementioning
confidence: 99%
“…Unsaturated FAs have been shown to inhibit the LPS-induced NF-κB signalling pathway in macrophages [25,34]. Moreover, monounsaturated FAs, such as oleate, protect against various lipotoxic effects of palmitate [35][36][37][38][39]. The protective effects of oleate are reported at concentrations lower or equimolar to that of palmitate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, including our own, have demonstrated that ER stress mediates the upregulation of scavenger receptors on macrophages, such as lectin-like oxidized LDL receptor-1 and CD36, and promotes foam cell formation (23,43). On the other hand, prolonged and severe ER stress triggers proapoptotic signals in macrophages, which in turn result in the instability of advanced atherosclerotic plaques (14,44).…”
Section: Hdl From Ms Patients Induces Oxidative Stress and Chop-mediamentioning
confidence: 99%